Influence of the addition of chlorhexidine diacetate on bond strength of a high-viscosity glass ionomer cement to sound and artificial caries-affected dentin - Becci, Ana Carolina De Oliveira; Marti, Luana Mafra; Zuanon, Angela Cristina Cilense; Brighenti, Fernanda Lourenção [UNESP]; Spolidório, Denise Madalena Palomari; Giro, Elisa Maria Aparecida (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
INTRODUCTION:The aim of adding chlorhexidine (CHX) to glass ionomer cements (GIC) is to improve their antibacterial property, but it may interfere with their bond to dentin.OBJECTIVE: To evaluate the influence of adding chlorhexidine diacetate at different concentrations to a high-viscosity GIC on its bond to sound and artificial caries-affected dentin.MATERIAL AND METHOD:Eighty human third molars were used, on which an area of dentin was exposed on the occlusal surface. Half of the specimens were kept sound and the other half were subjected to artificially induced caries. CHX was mixed with GIC powder at 0.5%, 1% and 2% (w/w). GIC without CHX was used as control. On each dentin surface a specimen measuring 1 mm in diameter and 1 mm high was made. The samples were kept at 37 °C and 100% humidity for 24 hours and subject to microshear testing. The results were analyzed using Kruskal-Wallis and Mann Whitney tests (α=0.05).RESULT:There was no significant difference between bond strength of sound and caries-affected dentin (p>0.05). For both substrate conditions, groups GIC, GIC+0.5% CHX and GIC+1% CHX showed statistically similar bond strength (p>0.05), and higher than that of GIC+2% CHX (p<0.025). Cohesive and mixed failures were predominant in all groups.CONCLUSION:The addition of 0.5% and 1% chlorhexidine did not result in negative changes in the bond strength of GIC to caries-affected and sound dentin.

INTRODUÇÃO:A adição da clorexidina (CLX) ao cimento de ionômero de vidro (CIV) visa melhorar a sua propriedade antibacteriana, podendo contudo interferir na adesão à dentina.OBJETIVO:Avaliar a influência da adição de diacetato de CLX em diferentes concentrações a um CIV de alta viscosidade, na sua adesão à dentina sadia e afetada por cárie artificial.MATERIAL E MÉTODO:Foram utilizados 80 terceiros molares, que tiveram a superfície de dentina exposta na face oclusal. Metade dos dentes foram mantidos hígidos e a outra metade foi submetida à indução artificial de cárie. A CLX foi misturada ao pó do CIV nas concentrações de 0,5%, 1% e 2%. O CIV sem CLX foi usado como controle. Em cada superfície dentinária foi confeccionado um espécime com 1 mm de diâmetro e 1 mm de altura. Estes foram mantidos a 37 °C com 100% de umidade por 24 horas, e, submetidos ao teste de microcisalhamento. Os resultados foram analisados pelos testes de Kruskal-Wallis e Mann Whitney (α=0,05).RESULTADO:Não houve diferença estatística entre os valores de resistência de união para dentina hígida e afetada (p>0,05). Para as duas condições do substrato, os grupos CIV, CIV+CLX 0,5% e CIV+CLX 1% apresentaram resistência de união estatisticamente semelhante (p>0,05), e superior ao CIV+CLX 2% (p<0,025). Houve predominância de fraturas mistas e coesivas do material para todos os grupos.CONCLUSÃO:A adição de CLX nas concentrações de 0,5% e 1% não influenciou negativamente na resistência de união de um CIV de alta viscosidade à dentina sadia e afetada por cárie.
Influência da adição do diacetato de clorexidina na resistência de união de um cimento de ionômero de vidro de alta viscosidade à dentina sadia e afetada por cárie artificial
Keywords: Glass ionomer cements; chlorhexidine; physical properties; dentin; Cimentos de ionômeros de vidro; clorexidina; propriedades físicas; dentina